Design of UWB Antenna With Multi slot for Wireless Communication - V.Prashanth, K; Sai Venkatesh, N; Umamaheswari, B; Mukesh, M; Praneeth, G; Ramya Latha, B; Shameem, Syed (International Journal of Engineering and Technology, 2018)
A Compact dual slot ultra-wide band (UWB) Antenna for WLAN and X-Band applications is proposed. The projected antenna is designed for the planar ultra-wide band (UWB) antenna and ultra-wide band (UWB) with two band dismissals. The proposed antenna overall size is 30x40x1.6. The antenna comprises of Rectangular patch imprinted on the Flame Resistant (FR4) substrate with 50â„¦ input impedance. FR-4 is a composite material made out of fiberglass fabric woven with an epoxy pitch cover that is fire safe (self-dousing). "FR" implies fire resistant, and means that the material meets the standard. This patch consists of dual slot one for WLAN and one for X-band Satellite Communication System. The antenna intended with return loss (RL) >= 10db and frequency ranges between 3.1 to 10.6 GHz with VSWR<2. The antenna works for the applications of wireless local area network (WLAN) system (5.15 â€“ 5.825 GHz), X-band downlink (7.25 - 7.75). The ultra-wide band frequency range for these wireless systems causes interference. To reduce the interference, band notching is done. The WLAN and X-Band satellite communication system bands are forbidden by inserting slots in the patch. The proposed antenna is having high gain at the pass bands while a sharp drop at the forbidden bands.Â Â